The Impact of the Cross-Border Communication Conflict on the Goverance Image in The Developing Country - Nasution, Belli; Rasyid , Anuar; ., Suyanto; Handoko, Tito; Suryana, Dodi (Journal of Ecohumanism, 2024)
Communication conflict can occur when there are misunderstandings between parties, particularly when language or cultural differences are involved. If the conflict is not effectively managed, the impact on the government’s image could lead to ongoing tensions and mistrust. On the other hand, if the government can manage and resolve this effectively, it could increase trust and support from the public. The research objectives were to analyze the conflict communication between the government and the community on moving products in the developing country. This study’s research method used descriptive qualitative to analyze the impact of the cross-border communication conflict on the government’s image. Data collection was carried out through interviews and observations. The informant investigated were ten people. The results showed the conflict between the government and the community in the trade flows of the Meranti archipelago country, communication of conflicts between the government internally and externally, and the community in the flow of goods across countries in the Meranti Islands Regency. The government hopes its citizens to obey the law by creating a tertiary flow of goods from abroad. Moreover, the image of the central government for assistance or making regulations regarding the flow of goods Cross-Border could be better.